2003
DOI: 10.1038/sj.npp.1300216
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Cognitive Performances During a Placebo Period and an Atypical Antipsychotic Treatment Period in Schizophrenia: Critical Examination of Confounds

Abstract: Although previous studies report cognitive improvement following atypical antipsychotic administration in schizophrenia (SC), few placebo-controlled within-subject studies with examination of confounds (symptom reduction, cooperation, learning, and outliers) have been reported. The present study examines the effects of atypicals and confounds upon cognition in SC. The hypothesis tested was that relative to placebo, atypicals as a general class of medication would elicit cognitive improvement in SC. In all, 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 44 publications
(59 reference statements)
0
32
0
2
Order By: Relevance
“…We found that treatment with an atypical but not a typical APD increased the numbers and densities of newly generated cells in the PFC and striatum. The ability of olanzapine but not haloperidol to increase the generation of new cells in the cortex is consistent with the therapeutic profiles of these drugs: many but not all studies suggest that atypical APDs are more effective in reducing negative symptoms and improving cognitive function, both of which have been associated with PFC dysfunction (Meltzer and McGurk, 1999;Geddes et al, 2000;Wahlbeck et al, 2000;Bilder et al, 2002;Conley and Kelly, 2002;Bobes et al, 2003;Davis et al, 2003a, b;Gur et al, 2003;Leucht et al, 2003;Lieberman et al, 2003b;Moncrieff, 2003;Rosenheck et al, 2003;Weickert et al, 2003;Woerner et al, 2003).…”
Section: Functional Implicationsmentioning
confidence: 65%
“…We found that treatment with an atypical but not a typical APD increased the numbers and densities of newly generated cells in the PFC and striatum. The ability of olanzapine but not haloperidol to increase the generation of new cells in the cortex is consistent with the therapeutic profiles of these drugs: many but not all studies suggest that atypical APDs are more effective in reducing negative symptoms and improving cognitive function, both of which have been associated with PFC dysfunction (Meltzer and McGurk, 1999;Geddes et al, 2000;Wahlbeck et al, 2000;Bilder et al, 2002;Conley and Kelly, 2002;Bobes et al, 2003;Davis et al, 2003a, b;Gur et al, 2003;Leucht et al, 2003;Lieberman et al, 2003b;Moncrieff, 2003;Rosenheck et al, 2003;Weickert et al, 2003;Woerner et al, 2003).…”
Section: Functional Implicationsmentioning
confidence: 65%
“…Crossover studies may be prone to complex carry-over effects, drug withdrawal effects, and time one-time two differences (Weickert et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…We found no differences in performance between the typical, atypical, and unmedicated subjects, which we believe is simply due to a low number of subjects in the atypical and unmedicated groups. There is much evidence to support the idea that atypical antipsychotics help certain types of cognitive processes, including verbal fluency, verbal memory, general intelligence, continuous performance test, and spatial working memory, among others (Harvey, Green, McGurk, & Meltzer, 2003;Weickert et al, 2003). It has also been found that certain atypical medications (e.g., olanzapine, risperidone, and quetiapine) have a more advantageous effect than typical medications (e.g., haloperidol) on such cognitive processes as attention, motor function, visuospatial tasks, immediate recall tasks, verbal memory, and verbal fluency (Keefe et al, 2006;Purdon, Malla, Labelle, & Lit, 2001;Velligan et al, 2002).…”
Section: Discussionmentioning
confidence: 99%